Nanoparticles-mediated delivery of herbal extract: Impact on inhibition advanced glycation end-product (AGEs): A systematic review - Astuti Febriana; Akrom; Mustofa (BIO Web of Conferences)
This systematic review compiles and analyzes research on the therapeutic efficacy of nanoparticle-mediated delivery systems for herbal extracts aimed at inhibiting the formation of Advanced Glycation End- products. A comprehensive search of PubMed and Google Scholar was conducted in accordance with the PRISMA systematic review statement guidelines included studies published within the past 10 years. Our examination spans several studies utilizing different nanoparticle formulations—such as gold, silver, and zinc oxide nanoparticles—and encapsulated herbal extracts, including Poria cocos, Nigella sativa, and curcumin, among others. The outcomes indicate that these nanocomplexes not only foster enhanced delivery and bioavailability of the herbal extracts but also significantly decrease inflammatory biomarkers and blood glucose levels, enhance antioxidant responses, and protect against cellular damage caused by oxidative stress. This review emphasizes the potential of nanoparticles to augment the therapeutic properties of herbal medicines for preventing and managing diabetic complications through the inhibition of AGEs formation.